Ἀγωνιζόμενοι and διαλεγόμενοι: Dramaturgy in the First Part of Plato’s Theaetetus - Theodoroudi, Lia (Ariadne, 2026)
Starting from the premise that the dramatic elements of Plato’s dialogues are philosophically significant, I attempt to show that the dramaturgy of the first part of Plato’s Theaetetus reflects its philosophical content. Using “Protagoras’” distinction between ἀγωνιζόμενοι (those who are in combat with each other) and διαλεγόμενοι (those who are in dialogue with each other) as a hermeneutic axis, I examine a number of Plato’s dramaturgical choices (dramatic setting, figures of speech, characterization, character development and interactions among characters) and I bring out their relation to the distinction and to Protagoras’ doctrine in general. It appears that Plato is using the dramaturgy of the dialogue to illustrate the philosophical points made by his characters in a clear, vivid, and direct way.